A contribuição da TV Escola em práticas pedagógicas alternativas no ensino religioso - Gera, Madalena Lopes Ferreira (2013)
This current research approach is the TV Escola (School TV) basing itself on Pedagogical Practices as alternatives in the context of new paradigms faced with the technological advances in communication. In this way, the reflection is delimited by the holistic pedagogical practice as the guide for a process of teaching-learning aimed at forming the human being as a whole. With these presuppositions in view the research was delineated by the proposed dialog as to the integration of education, its contemporaneity and the contribution of the TV Escola to Religious Education, given the reach and possibilities in society and culture through the TV Escola. The conceptual formulation of the approximation of TV Escola with Religious Education was oriented by the formation of the professor, and that this professor might be prepared to work within diversity and globalization. And with this propitiate a propositional education to grant the student a minimum of knowledge for educational and social use and absorption through the know-how which the children and youth of today, in general, have of the new technologies. Allegedly, TV is a technology of broad reach. Thus, as conclusions, propositional elements were listed of the TV Escola and Religious Education, seeking new perspectives of changes aiming at the territoriality and promotion of religious and thought diversity. With this the TV is presented as being more than simple technological innovation, but as an equipment of knowledge, a metaphor of a new regime of teaching characterized by fluidity and interactivity.